Cationic DDA/TDB liposome as a mucosal vaccine adjuvant for uptake by dendritic cells in vitro induces potent humoural immunity. (31st October 2018) - Qu, Wenjing; Li, Na; Yu, Rui; Zuo, Wenbao; Fu, Tingting; Fei, Wenling; Hou, Yanhui; Liu, Yanhua; Yang, Jianhong
Abstract: The cationic dimethyldioctadecylammonium/trehalose 6, 6, 9-dibehenate (DDA/TDB) liposome is as a strong adjuvant system for vaccines, with remarkable immunostimulatory activity. The mucosal administration of vaccines is a potential strategy for inducing earlier and stronger mucosal immune responses to infectious diseases. In this study, we assessed whether the intranasal administration of cationic DDA/TDB liposomes combined with influenza antigen A (H3N2) can be used as a highly efficacious vaccine to induce mucosal and systemic antibody responses. Confocal laser scanning microscopy and a flow-cytometric analysis showed that the uptake of the cationic DDA/TDB liposome carrier was significantly higher than that of neutral 1, 2-distearoyl-sn-glycero-3-phosphocholine/cholesterol (DSPC/Chol) or cationic 1, 2-dioleoyl-3-trimethylammonium-propane/3β-( N -[ N ′, N ′-dimethylaminoethane]-carbamoyl (DOTAP/DC-Chol) liposomes. Our results indicate that the cationic DDA/TDB liposome is more effective in facilitating its uptake by dendritic cells (DCs) in vitro than the DSPC/Chol or DOTAP/DC-Chol liposome. DCs treated with DDA/TDB liposomes strongly expressed CD80, CD86, and MHC II molecules, whereas those treated with DSPC/Chol or DOTAP/DC-Chol liposomes did not. C57BL/6 mice intranasally immunized with H3N2-encapsulating cationic DDA/TDB liposomes had significantly higher H3N2-specific s-IgA levels in their nasal wash fluid than those treated with other formulations. The DDA/TDB liposomes also simultaneously enhanced the serum IgG IgG2a, IgG1, and IgG2b antibody responses. In summary, DDA/TDB liposomes effectively facilitated their uptake by DCs and DCs maturation in vitro, and induced significantly higher mucosal IgA, systemic IgG, IgG1, and IgG2b antibody titres than other formulations after their intranasal administration in vivo . These results indicate that DDA/TDB liposomes are a promising antigen delivery carrier for clinical antiviral applications.